The Epimedium wushanense (Berberidaceae) species complex, with one new species from Sichuan, China - Zhang, Yanjun; Dang, Haishan; Li, Jianqiang; Wang, Ying (Phytotaxa, 2014)
Epimedium wushanense (Berberidaceae) as treated in the Flora of China includes four species similar in leaflet shape: E. wushanense, E. ilicifolium, E. jinchengshanense (sp. nov.), and E. pseudowushanense. Its seven type specimens represent three of the four species. In the present paper, E. wushanense is identified according to morphological characters of its holotype. Except for four of the seven type specimens belonging to E. wushanense and E. ilicifolium, the remaining three specimens represent a new species, E. jinchengshanense. Furthermore, E. wushanense from Guangxi and Guizhou as treated in the Flora of China is recognized as E. pseudowushanense. Epimedium wushanense, E. ilicifolium, E. jinchengshanense, and E. pseudowushanense differ by their distributions and flowers. Based on the floral characters, E. jinchengshanense is grouped into ser. Dolichocerae, E. wushanense is adjusted from ser. Dolichocerae to ser. Davidianae, and E. ilicifolium is moved from ser. Davidianae to ser. Dolichocerae.